Contrast Enhancement and Image Quality Influence Two- and Three-dimensional Echocardiographic Determination of Left Ventricular Volumes: Comparison With Magnetic Resonance Imaging. Issue 13 (March 2019) - Jenner, Jonas; Sörensson, Peder; Pernow, John; Caidahl, Kenneth; Eriksson, Maria J
Purpose: To evaluate the effect of image quality and contrast enhancement (CE) on left ventricular (LV) volume determination by two- (2D) and three-dimensional (3D) echocardiography (2DE/3DE). Methods: We studied 32 post-myocardial infarction (MI) patients without (2DE/3DE) and with CE (CE2DE/CE3DE), in comparison with cardiac magnetic resonance imaging (CMR). Results: Two-dimensional echocardiography showed the largest negative bias versus CMR for diastolic and systolic volumes (−59, −28 mL, respectively) with lower biases for CE2DE (−37, −22 mL), 3DE (−31, −17 mL), and CE3DE (−17, −11 mL). Bias for ejection fraction (EF) ranged from −2.1% for 2DE to +1.4% for CE3DE. Agreement (intraclass correlation coefficient, ICC) for EF between CMR and 3DE (0.86 without and 0.85 with contrast) was better than for 2DE (0.73 without and 0.69 with contrast). The inter-/intra-observer coefficients of variation for EF varied from 16%/10% (2DE) to 6.9%/6.6% (CE2DE), and 8.3%/4.8% (3DE) to 6.7%/6.8% (CE3DE), respectively. The agreement (ICC) with CMR for EF measured by 2DE/3DE changed from 0.64/0.84 with poor image quality to 0.81/0.87 with moderate to good image quality. Conclusions: Three-dimensional echocardiography was more accurate than 2DE for estimating LV volumes, with less inter-/intra-observer variability in EF values. Contrast enhancement improved accuracy for both 2DE and 3DE and improved the inter-observer variability of EF estimates for 2DE and 3DE. Image quality had more impact on the agreement of EF values with CMR for 2DE than for 3DE. Our results emphasize the importance of using the same technique for longitudinal studies of LV EF and specially LV volumes.